Development and application of a borehole stress meter in rocks surrounding the roadway, based on optical-fiber sensing technology - Xie, Xiaoping; Fang, Xinqiu; Liu, Hongyang; Xing, Xiaopeng; Liang, Minfu; Wu, Gang; Chen, Ningning (Frontiers in Earth Science, 2023)
The work designed CS-FBG(cystic structural fiber grating) borehole stress meter suitable for the mining stress monitoring of surrounding rock masses in underground roadways in the coal mine by fiber sensing technology and verified its performance through rig-site utilization. The main conclusions are as follows: (1) The mechanical model of the surrounding rocks of the borehole was constructed by theoretical analysis, and the interaction between surrounding rocks and borehole stress meter was analyzed. The results showed that the monitoring accuracy of borehole stress meter was improved by increasing the initial stress and elasticity of borehole stress meter. (2) CS-FBG borehole stress meter and TS-FBG(tubular structural fiber grating) borehole stress meter were designed by combining the sensing principle and sensing characteristics of fiber Bragg grating, and their performance was tested by experiments. Initial stress and the elasticity of the borehole stress meter affected the precision of stress monitoring. The CS-FBG borehole stress meter is more suitable for the stress monitoring requirements of the surrounding rock of the coal mine roadway through testing and comparative analysis, compared with the TS-FBG borehole stressmeter. (3) The rig-site utilization results showed that there were obvious stress growth zone and stress peak zone in the mining-stress change curves of each measuring point on the two sides of the track roadway in the process of mining the test working face. Besides, there were four stages of rapid rise, uniform growth, rapid rise to the peak, and rapid decline. Maximum stress monitored by the second station was 18.5 MPa, and the influence range of stress was over 140 m. Maximum stress monitored by the first measuring station was 19 MPa; the influence range of stress was about 80 m; the peak stress position was about 20 m in front of the coal wall. The design of the CS-FBG borehole stress meter was proved to be reasonable through the rig-site utilization. Performance is stable and reliable, and the successful operation of the field monitoring has achieved the expected effect of field monitoring.